Linking herders to carbon markets in China - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
While smallholder farmers and communities adopt agricultural practices that provide carbon sequestration benefits, it can be difficult for them to reap economic rewards by accessing carbon markets. For example, effective grassland management can substantially improve livestock productivity and also sequester carbon, providing a double win. However, the lack of approved standards for monitoring and accounting the carbon sequestration prevents farmers from tapping into carbon markets. The absence of tangible economic incentives can limit adoption of practices capable of restoring degraded grasslands.